THE CONCEPT OF GUNA IN SANSKRIT POETICS - Samani, Nirali; Santhanam, Lalitha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the evolution and significance of the concept of Guṇa in Sanskrit poetics, tracing its development from early foundational texts to its philosophical reorientation in later aesthetic theory. Guṇa, often translated as “quality” or “virtue,” refers to the intrinsic poetic qualities that give literary works emotional depth, stylistic beauty, and expressive power. Through a detailed examination of classical sources -including Bharata’s Nāṭyaśāstra, Daṇḍin’s Kāvyādarśa, Vāmana’s Kāvyālaṅkārasūtravṛtti, and Ānandavardhana’s Dhvanyāloka -the paper outlines the shifting interpretations of Guṇa, from its initial classification as a technical aspect of style to its ultimate subordination to Rasa - aesthetic emotion in the Dhvani school. The study also distinguishes Guṇa from Alaṅkāra – ornamentation and analyzes its relationship to other poetic elements such as śabda - sound, artha - meaning, and rīti - style. Ultimately, the paper argues that Guṇa serves not merely as a marker of rhetorical excellence but as an integral component of the poetic experience, valued most when it enhances emotional suggestion and artistic unity.